2017
DOI: 10.1177/0963689717714341
|View full text |Cite
|
Sign up to set email alerts
|

Dexamethasone Attenuates the Enhanced Rewarding Effects of Cocaine Following Experimental Traumatic Brain Injury

Abstract: Clinical studies have identified traumatic brain injury (TBI) as a risk factor for the development of cocaine dependence. This claim is supported by our recent pre-clinical studies showing enhancement of the rewarding effects of cocaine in mice sustaining moderate controlled cortical impact (CCI) injury during adolescence. Here, we test the efficacy of dexamethasone, an anti-inflammatory corticosteroid, to attenuate augmentation of the behavioral response to cocaine observed in CCI-TBI animals using the condit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
39
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 34 publications
(44 citation statements)
references
References 62 publications
1
39
0
Order By: Relevance
“…As reports by Shah et al and Alhilali et al also observed white matter injury in the NAc of TBI patients 39, 40 , similar immune cell activation and accumulation may occur in all white matter tracts including the anterior commissure, which runs directly through the NAc. In fact, as mentioned, our recent studies show that reactive microglia and chronic neuroinflammation occur not only at the cortical site of injury, but also in distal brain regions like the PFC and NAc (Figure 2) 21, 41 .…”
Section: Neuroinflammationmentioning
confidence: 63%
See 4 more Smart Citations
“…As reports by Shah et al and Alhilali et al also observed white matter injury in the NAc of TBI patients 39, 40 , similar immune cell activation and accumulation may occur in all white matter tracts including the anterior commissure, which runs directly through the NAc. In fact, as mentioned, our recent studies show that reactive microglia and chronic neuroinflammation occur not only at the cortical site of injury, but also in distal brain regions like the PFC and NAc (Figure 2) 21, 41 .…”
Section: Neuroinflammationmentioning
confidence: 63%
“…As previous studies have shown that immunosuppressive agents can modulate the severity of substance abuse behavior 72 , we wanted to determine whether neuroinflammation plays an important role in enhancing the rewarding effects of cocaine following adolescent brain injury. Our results show that administration of a synthetic, anti-inflammatory glucocorticoid receptor agonist (dexamethasone) significantly attenuates the enhanced rewarding effects of cocaine and returns drug-seeking behavior to control levels 41 . Furthermore, we show that dexamethasone therapy significantly reduced the expression of select immune response genes (i.e.…”
Section: Neuroinflammationmentioning
confidence: 76%
See 3 more Smart Citations